2022
DOI: 10.1002/adfm.202201959
|View full text |Cite
|
Sign up to set email alerts
|

An Underwater Long‐Term Strong Adhesive Based on Boronic Esters with Enhanced Hydrolytic Stability

Abstract: Boron‐based adhesives have attracted considerable attention in recent years due to their strong adhesive behavior and reversible capacities. However, limited by the humidity sensitivity and poor dynamicity, it remains challenging for the boron‐based adhesive materials to realize strong and long‐term adhesion underwater. In this study, a novel boronic ester (BN‐6) with changeable ring strain induced by the heat‐responsive BN coordination bond is designed and synthesized. Due to the low strain of the six‐member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 60 publications
0
54
0
Order By: Relevance
“…Following the procedure in Fig. 2A , the adhesion performances between various separated substrates bonded by the P(DPOP-Si) adhesive were monitored in detail ( 40 ). Note that the adhesive with a small contact area (about 2 cm × 1 cm) on the smooth glass substrate could hold a 1-kg weight easily ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the procedure in Fig. 2A , the adhesion performances between various separated substrates bonded by the P(DPOP-Si) adhesive were monitored in detail ( 40 ). Note that the adhesive with a small contact area (about 2 cm × 1 cm) on the smooth glass substrate could hold a 1-kg weight easily ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proved that the N atom can coordinate with the B atom of boroxine, and internal and external coordination bonds can form. 51,52 B-N internal coordination bond can enhance the boroxine bond, while the B-N external coordination bond can weaken the boroxine bond. Therefore, the B-N internal coordination bond can enhance the hydrolytic stability of boroxine.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the B–N internal coordination bond can enhance the hydrolytic stability of boroxine. 52 For PDMS-DPBA-5000, the position of the N atom makes the B–N internal coordination bond not to form. In addition, from the 11 B NMR spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al further revealed the effect of the ring size of N-coordinated boronate ester on the properties of the materials by tuning the structure of tridentate ligands . A six-membered, N-coordinated boronate ester (BN-6) was prepared and applied in a polymeric adhesive (Figure a).…”
Section: N-coordinated Boronic Acids or Esters In Healable And Reproc...mentioning
confidence: 99%
“…(a) Synthesis route of hermosets based on six-membered N-coordinated boronic ester (TBN6) and schematic illustration of multiple dynamic bonds in the polymer network. (b) The variable temperature 11 B NMR spectra and dynamic configuration transformation of boronic esters BN-6 (top) and BN-5 (below) during heating (500 MHz, DMSO- d 6 ) . Panels (a,b) were reproduced with permission from ref .…”
Section: N-coordinated Boronic Acids or Esters In Healable And Reproc...mentioning
confidence: 99%